Shakespeare law, and marriage - Sokol, B.J (Cambridge University Press, 2003)
Combining legal, historical and literary approaches to the practice and theory of marriage in Shakespeare's time, this study discovers a broad range of information in a selection of Shakespeare's plays. Jerry and Mary Sokol approach the legal history of marriage as part of cultural history. The household was viewed as the basic unit of Elizabethan society, but many aspects of marriage were controversial, and the law was uncertain and confusing. The Sokols' analysis reveals much about Shakespeare's age as well as his work.